KETERLIBATAN MASYARAKAT DI OBJEK WISATA PALAWA’: Studi Kasus Desa Wisata Palawa’ Kabupaten Toraja Utara - Hudiono, Rini Kartika; -, Eka (Universitas Kristen Satya Wacana, 2020)
Benchmarks of the success of a tourist attraction can be seen from the involvement of the community. Community based tourism is a form of tourism development that aims to empower people in independence and decision making. This study aims to determine and analyze the involvement of local communities in the development of tourism in the Palawa’ Village and identify any obstacles that affect the involvement of local communities in the development of Palawa’ Village. This research was conducted for 6 months from September 2019. Researchers used data collection methods through interviews, observations, and documentation to the management or manager of Palawa’ Village and the community and used a descriptive qualitative approach. The results of this study indicate that lack of community involvement in Palawa’ Village. This is because not all communities have a traditional house (Tongkonan) so they cannot be directly involved and only become spectators in every activity that is held. The internal factors that influence community involvement are the low quality of education so that limited knowledge is very influential on how to manage good tourism businesses and existing entrepreneurial management knowledge. While externally, there is a lack of cooperation between tourism managers and outsiders such as the Culture and Tourism Office, Regional Planning Agency (Bappeda), Youth Organization and Pokdarwis. Researchers provide recommendations to managers to provide counseling or training to the community so that community knowledge about tourism is higher, Involving all communities and stakeholders in the development of Palawa’ Village attractions and increasing good cooperation between managers and outsiders.